Impact of concentration of Bi2O3 on gamma ray shielding efficiency of BaTiO3 composite ceramics - Rama Kumar Nodagala; Tejeswara Rao Ponnada; Balaji Rao Ravuri (Chemical Physics Impact)
This study primary goal is to provide information on the structural changes and improved radiation shielding qualities of BaTiO3 (barium titanate) ceramics that have been added to Bi2O3 (bismuth trioxide) compound, which is made using a solid-state reaction technique. The tetragonal perovskite structure of the BaTiO3 ceramics was verified by both Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis before and after the addition of xBi2O3 at concentrations of x = 0,2,4,6, and 8 wt%. The FESEM technique was used to investigate the prepared samples morphological study. The results showed that as concentration enhanced, the grain size reduced from 49.4 nm to 43.1 nm, and the findings agreed with the XRD data. Radiation attenuation between photon energy range 356 keV to 1333 keV was estimated using prepared samples by scintillation detector NaI(TI) from radioactive sources such as 133Ba, 60Co, and 22Na. An essential attenuation property is the mass attenuation coefficient (MAC), which is calculated using acquired linear attenuation coefficient (LAC) values. Other characteristics related to radiation shielding parameters such as mean free path (MFP), half-value layer (HVL), tenth-value layer (TVL), effective atomic number (Zeff), effective electron density (Neff), and effective conductivity (Ceff) were also assessed. The theoretical values were obtained from Phy-X/PSD software and compared with experimental values, and a slight difference was found between theoretical and experimental values. Finally, compound BaTiO3-xBi2O3 with x = 8wt%, that is, the BTBi5 sample showed the highest shielding properties compared with other samples due to its high density after enhancing the Bi2O3 concentration.